Development and use of species-specific oligonucleotide probes for differentiation of Streptococcus uberis and Streptococcus parauberis. - Bentley, R W (1993)
Oligonucleotide probes specific for 16S rRNA and capable of differentiating Streptococcus uberis and S. parauberis from each other and other esculin-hydrolyzing streptococci were developed. Use of a mini-RNA extraction technique for gram-positive cocci associated with bovine mastitis has allowed the probes to be used for identification of esculin-hydrolyzing streptococci from two dairy herds at the Institute for Animal Health, Compton, United Kingdom. One hundred seventy-nine of 206 isolates were identified as S. uberis, 3 were identified as S. parauberis, and 24 were not identified. Isolates not identified by the probes were tested biochemically and found to be mainly Enterococcus faecium, E. faecalis, or S. bovis.